Stravinsky and His World - Levitz, Tamara, 1962- (Book collections on Project MUSE., 2013)
Stravinsky and His World brings together an international roster of scholars to explore fresh perspectives on the life and music of Igor Stravinsky. Situating Stravinsky in new intellectual and musical contexts, the essays in this volume shed valuable light on one of the most important composers of the twentieth century. Contributors examine Stravinsky's interaction with Spanish and Latin American modernism, rethink the stylistic label ""neoclassicism"" with a section on the ideological conflict over his lesser-known opera buffa Mavra, and reassess his connections to his